Gabon : First Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the First Review Under the Stand-By Arrangement (SBA) on Gabon focuses on economic developments and policies. The economy is little diversified and heavily dependent on oil production, which is on a downward trend; the debt burden is high; and social indicators are weak. The program supported by the 14-month SBA aims at promoting non-oil GDP growth through wide-ranging structural reforms, while sustaining fiscal adjustment and improving public expenditure management. Progress has been made on the structural front, notably in the forestry sector and in the areas of privatization and budgetary management.